Corrosion mechanisms of 316L stainless steel in supercritical water: The significant effect of work hardening induced by surface finishes. (15th August 2019) - Payet, Mickaël; Marchetti, Loïc; Tabarant, Michel; Jomard, François; Chevalier, Jean-Pierre
Highlights: Oxidation behavior of 316L SS in SCW strongly depends on subsurface work-hardening. Ionic image highlights reaction interfaces of double-layered oxides. Reaching a hardening threshold leads to a considerable thinning of the oxide scale. Diffusion of hydrogen through the oxide scale leads to H uptake by the alloy. Abstract: The oxidation of 316 L stainless steel in hydrogenated supercritical water at 600 °C is strongly dependent on the effects of work hardening induced by surface finishes. The oxide scale formed under these conditions is always double-layered with an external layer of Fe-rich oxides. However, when a hardening threshold is reached, a switch in oxidation mechanisms leads to a considerable thinning of the oxide scale. This thinning results from the formation of a Cr-rich internal oxide layer that acts as a diffusion barrier against ionic species responsible for its growth but also against Fe cations implied in the external layer growth.